PENGARUH MODEL PEMBELAJARAN INKUIRI TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV SEKOLAH DASAR - Putri Pikrin, Salsabila; Nana Sutarna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of inquiry learning models on the learning outcomes of science in grade IV of elementary school. This research method uses quantitative research, using experimental design, the type of experimental design used is quasi-experiment with a non-equivalent control group design, the sampling technique used in this study is using the nonprobability sampling technique. The sampling technique is saturated sampling. The research sample consisted of two classes, namely the experimental class consisting of 25 students (grade IV A of SD Negeri 1 Darma) and the control class consisting of 28 students (grade IV B of SD Negeri 1 Darma). Data were collected through pre-test and post-test tests. The learning outcomes of grade IV students in the subject of science before the application of the inquiry model in the experimental class got an average score of 62, while the learning outcomes of grade IV students after the application of the inquiry model in the experimental class got an average score of 85. The learning outcomes of students in the control class before conventional learning took place, students got an average score of 60, while the learning outcomes of students after conventional learning took place got an average score of 72. Therefore, the results of the calculation showed that the average score of the experimental class was better than the average of the experimental class. With this, the results of this study indicate an increase in the learning outcomes of grade IV science in the experimental class and the control class. So it can be concluded that the inquiry learning model can improve student learning outcomes in science lessons in grade IV Elementary School.